An audit of radiotherapy patient doses measured with in vivo semiconductor detectors - Adeyemi, A; Lord, J (British journal of radiology, 1997)
Uncertainties exist both in the basic data from which a radiotherapy plan is produced and in the process whereby such a plan is translated into the patient set-up during treatment. Individual parts of the radiotherapy process are subject to checks, but the overall accuracy of treatment delivery is not routinely evaluated. In vivo dosimetry by means of a semiconductor detector system can be used to measure the cumulative error in the radiotherapy treatment dose delivered. A direct patient dosimetry system was commissioned and introduced in January 1993 for the routine evaluation of the doses patients receive. Since its introduction a total of 1000 patients have been monitored for a range of radiotherapy applications, comprising 300 breast treatments (6 MV X-rays), 150 head and neck treatments (6 MV X-rays) and 550 pelvis. abdomen and thorax treatments (10 MV X-rays). The results of this audit show that less than 5% of all patients monitored gave a systematic error more than +/- 5% for a single field, or more than +/- 2.5% for the "estimated overall error" in the isocentre dose. The causes of these errors were identified and appropriate action taken where necessary. It is suggested that this method could be used routinely in radiotherapy treatment to assess the overall performance of the treatment process.